Gender Differences in the Prediction of Children's Weight Status from Measures of Non-Eating and Eating Self-Regulation. (29th May 2020) - Hughes, Sheryl; Power, Thomas; Fisher, Jennifer; O'Connor, Teresia; Micheli, Nilda
Abstract: Objectives: The goal of this study was to investigate gender differences in the prediction of BMI z-scores in children ages 7 to 9. Predictors included well-known measures of non-eating and eating self-regulation assessed during the preschool years (ages 4 to 5). Methods: Participants were part of a longitudinal study examining eating behaviors in Hispanic families with low-income levels living in a large urban city in southeast United States. Children and their parents were seen at Time 1 (ages 4–5), Time 2 (ages 5 ½-6 ½), and at Time 3 (ages 7–9). One hundred and thirty families had data on all variables needed for the current analyses. Both parent-report questionnaires as well as observational protocols were used to measure child self-regulation. Parent-report questionnaires included satiety responsiveness and food responsiveness (two child eating self-regulatory measures known to be associated with childhood obesity) and effortful control (a self-regulatory aspect of child temperament). Observational protocols included eating in the absence of hunger (a well-known child eating self-regulation measure) and executive functioning, delay of gratification, and emotional regulation (all measures of non-eating self-regulation). Height and weight were objectively measured on the children. Regressions were conducted to predict child weight status at ages 7 to 9 from measures of child eating and non-eating self-regulatory processes. Data on boys and girls were analyzed in different regressions. Parent-reported measures were analyzed separately from observational measures. Results: Only the regression for girls, predicting Time 3 child BMI z-scores from observational measures, showed significant effects over and above the effects of Time 1 child BMI z-scores. Eating in the absence of hunger (eating self-regulation) positively predicted whereas delay of gratification (non-eating self-regulation) negatively predicted changes in girls' BMI z-scores overtime. Conclusions: The results of this study point to the importance of addressing non-eating self-regulation as well as eating self-regulation in future family-focused childhood obesity initiatives, especially those focused on Hispanic families with young children. Funding Sources: Research was funded by the National Institutes of Health (R01 HD062567).